THE ORGANIZATION AND MANAGEMENT OF GRID INFRASTRUCTURES. - Bird, Ian; Jones, Bob; Kee, Kerk F. (Computer (00189162), 2009)
This article discusses research into the use of grid computing technology to facilitate data-intensive analysis in research fields such as high energy physics. The development of a grid computing system by the European Organization for Nuclear Research to process data for the Large Hadron Collider (LHC) is described. The role of this virtual organization in the processing of data from the LHC is noted. Other data-intensive research projects in fields such as astrophysics, finance, and high throughput drug screening that use the grid developed for the LHC are also noted.